DEALER CLASSIFICATION AND TACTICAL MARKETING OF PT HINO FINANCE INDONESIA (Fakultas Ekonomi Universitas Wisnuwardhana, 2022)
Abstract : PT Hino Finance Indonesia is a financial service company that is also a Captive Finance from PT Hino Motor Sales Indonesia. During the period of 2015-2017, PT Hino Finance Indonesia always did not achieve the targets which set by the company's management. Marketing strategy which carried out by PT Hino Finance Indonesia is still not effective enough to compete in the current Hino financing market. The marketing mix strategy that is carried out is not focused on dealers who contribute well to the company. This study aims to classify which dealers have a sales contribution and good non-performing loan (NPL) performance for PT Hino Finance Indonesia. The next goal is that the results of this study are expected to be an alternative strategy for company management. This research was conducted by using survey method of in-depth interviews with the marketing mix variables that have been carried out by the Company at this time. The informants from this study were Hino sales manager and dealer manager of PT Hino Finance Indonesia. From the results of the interview cluster analysis was conducted using the Ward & K-Means Cluster method in determining which dealers were suitable given the 4P marketing mix strategy (Product, Price, Promotion, Place). Keywords: PT Hino Finance Indonesia, Methods of Ward & K-Means Cluster, Marketing Mix. Abstrak : PT Hino Finance Indonesia merupakan perusahaan jasa keuangan yang juga merupakan Captive Finance dari PT Hino Motor Sales Indonesia. Selama periode 2015-2017, PT Hino Finance Indonesia selalu tidak mencapai target yang telah ditetapkan oleh manajemen perusahaan. Strategi pemasaran yang dilakukan PT Hino Finance Indonesia masih belum cukup efektif untuk bersaing di pasar pembiayaan Hino saat ini. Strategi bauran pemasaran yang dilakukan tidak terfokus pada dealer yang memberikan kontribusi baik bagi perusahaan. Penelitian ini bertujuan untuk mengklasifikasikan dealer mana yang memiliki kontribusi penjualan dan kinerja kredit bermasalah (NPL) yang baik untuk PT Hino Finance Indonesia. Tujuan selanjutnya adalah hasil penelitian ini diharapkan dapat menjadi alternatif strategi bagi manajemen perusahaan. Penelitian ini dilakukan dengan menggunakan metode survei wawancara mendalam dengan variabel bauran pemasaran yang telah dilakukan oleh Perseroan saat ini. Informan dari penelitian ini adalah manajer penjualan Hino dan manajer dealer PT Hino Finance Indonesia. Dari hasil analisis cluster wawancara dilakukan dengan menggunakan metode Ward & K-Means Cluster dalam menentukan dealer mana yang cocok diberikan strategi bauran pemasaran 4P (Product, Price, Promotion, Place).Kata kunci: PT Hino Finance Indonesia, Metode Ward & K-Means Cluster, Bauran Pemasaran.